KONTRIBUSI MAḤFŪẒ AL-TARMASĪ DALAM PENGKAJIAN HADIS DI INDONESIA - Ahmad Faisal (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2018)
Modern Hadīṡ experts are still very minimal, even there are still many muḥaddiṡ figures who are not yet known by the public. One of them was Shaykh Muḥammad Maḥfūẓ ibn Abdullāh ibn Abd alMannān al-Tarmasī al-Jāwī al-Makkī al-Syāfiʻī. Shaykh Muḥammad Maḥfuẓ compiled the book of Jurisprudence and Proposals, Hadīṡ and also al-Qirā’at. The contribution of Maḥfūẓ al-Tarmasī's thoughts in the study of Hadīṡ in Indonesia can be seen in the book, first; Al-Minḥah al-Khairiyyah. Second, Manhaj Żawī al-Naẓar fī Syarḥ Manẓūmati ʻIlm al-ʻAṡar. Third, Transmission of Sanad in the book entitled Kifāyatu al-Mustafīd fīmā ʻalā min al-Asānīd by the work of Muhammad Yāsin alFānānī. Maḥfuẓ al-Tarmasī's work entitled Manhaj Żawī al-Naẓar fī Syarḥ Manẓumati ʻIlm al-ʻAṡar is a book that is used as a reference in many universities such as Egypt, Morocco, Mecca and Indonesia. This one work is the explaination book from the great work of the world Hadīṡ scholars, namely Alfiyyah al-Suyūṭī who discusses the science of Hadīṡ. The difficulty in understanding the naẓm-naẓm contained in the work of al-Suyūṭī, makes Maḥfuẓ al-Tarmasī challenged and then agrees with it with the intention to be more easily understood and understood by students and lovers of Hadīṡ knowledge in general.